2020
DOI: 10.1007/978-3-030-43332-1_12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compatibility and Dimensionality of Carbon Nanofillers on Cement Composites

Abstract: h i g h l i g h t sCarbon allotropes of various dimensionalities are explored in reinforcing cement. Effect of nanofillers on fresh and hardened states of cement composites is investigated. Compatibility and dimensionality of nanofillers play a crucial role in reinforcing cement composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Results showed that the incorporation of an optimum concentration of CNMs into the CSS increased the hydration products and specifically raised the amount of the CH and C-S-H gel [ 48 , 49 ]. The maximum quantity of cement hydration products was achieved by the addition of 0.1% hybrid CNT/GNP, and an excessive increase in the CNM concentration caused the reduction in hydration.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the incorporation of an optimum concentration of CNMs into the CSS increased the hydration products and specifically raised the amount of the CH and C-S-H gel [ 48 , 49 ]. The maximum quantity of cement hydration products was achieved by the addition of 0.1% hybrid CNT/GNP, and an excessive increase in the CNM concentration caused the reduction in hydration.…”
Section: Resultsmentioning
confidence: 99%
“…While storage does not add value, the use of carbon fillers in concrete and for other construction purposes could meet the criteria for long-term removal of the carbon from the atmosphere. Carbon-reinforced cement could also contribute to material savings and reduced energy demand [121][122][123].…”
Section: Hydrogen Production By Methane Pyrolysismentioning
confidence: 99%